Internal consistency reliability and construct validity of the safety questionnaire for ride-hailing car - Daud, Mohd Shazwan; Osman, Syuhaily; Hashim, Ahmad Hariza; Abd Rahim, Husniyah (Human Resource Management Academic Research Society, 2023)
Road traffic accidents involving ride-hailing car (RHC) have become more prevalent in Malaysia in recent years. Therefore, the present study aims to develop a reliable and valid questionnaire for assessing the safety performance of RHC in Malaysia. Three risk domains were identified in the literature, comprising driving behaviour factors, vehicle safety factors, and road environment factors. In these risk domains, a total of 32 risk indicators were selected, and these items were subsequently added to the questionnaire. Afterwards, these questionnaires were randomly distributed to 350 RHC passengers. To have a reliable and valid questionnaire, the internal consistency reliability by Cronbach’s alpha as well as construct validity by exploratory factor analysis were used. The finalized findings showed that all of the measurements have excellent reliability standards between 0.823 and 0.925. From the results of construct validity tests, there were three factors extracted from 21 risk indicators. Consequently, a number of questions were amended to better quantify the constructs. The finalized RHC safety questionnaire is a valid and an internally reliable tool for assessing the safety performance of RHC in Malaysia.